External Economic Effects of Air Transport Development due to the Liberalization - Oksana Ovsak; Maryna Vysotska (Communications - Scientific letters of the University of Zilina, 2021)
The paper is devoted to research of the impact of gradual liberalization of aviation market on the country’s air transport industry development and on formation of external economic components of the country’s GDP connected to it directly: export and import of air transport services. The study of the relationship between the operation indicators of air transport and formed external economic effects has been conducted using comparative, correlative and regression analysis based on the statistical data of Ukraine, which has its own air transport industry and is on the path of aviation liberalization. A strong dependence of the export of air transport services on the total number of international flights and its passengers was revealed. This determines the feasibility of tracking the external economic effects in the design of changes on directions and means of further development of country’s air transport sector.